A structure/catalytic activity study of gold(I)-NHC complexes, as well as their recyclability and reusability, in the hydration of alkynes in aqueous medium - Fernandez, Gabriela Araceli (2016)
We conducted a structure/catalytic activity study of water-soluble gold(i) complexes-supporting sulfonated NHC ligands-in the hydration of alkynes in pure water or water nsp;:nsp;methanol (1nsp;:nsp;1), as well as their recyclability. Comparative studies were carried out with the addition of different silver salts. Our results indicate that the bulkier complex is the most effective and that the addition of methanol as co-solvent not only shortens reaction times but also stabilizes the less bulky complexes.